Elucidation Of The Molecular Mechanisms Of Orthosiphon Aristatus Extract In Non-Alcoholic Fatty Liver Disease - Al Shehade, Salah Abd Alrazak (2023)
Non-alcoholic fatty liver disease (NAFLD) is the most common form of liver disease, beginning with simple hepatic steatosis and potentially leading to hepatic inflammation, fibrosis, and cirrhosis. Despite extensive research on NAFLD, there is no approved standard therapy for it as of now. Natural agents could potentially serve as alternative or supportive therapeutic options. Orthosiphon aristatus (Blume) Miq, a traditional plant in Southeast Asia, holds promise due to its potential to mitigate obesity and hyperglycaemic conditions. A plethora of chemical constituents in the ethanolic extract of O. aristatus (EOA) have been identified in previous studies, underscoring its potent antioxidant properties and broad ethnopharmacological usage. This study evaluated the potential anti-NAFLD effects of the EOA using a variety of in vitro, in vivo, and in silico methods. This included feeding C57BL/6 mice a high-fat diet, inducing multilineage 3D spheroids of HepG2 and LX-2 cells using palmitic-oleic acid induced-NAFLD, and employing various bioinformatics tools, such as molecular docking, to identify the pharmacokinetic and pharmacodynamic properties of the bioactive compounds of the EOA. Our findings identified 20 bioactive compounds corresponding to 45 potential NAFLD-related targets. Mice fed with the standardized EOA (400 mg/kg) for eight weeks showed inhibited NAFLD progression. Significant reductions in liver enzymes such as alanine aminotransferase and aspartate transaminase, as well as serum levels of glucose, insulin, total cholesterol, triglycerides, and low-density lipoprotein were observed.